2013
DOI: 10.1111/jonm.12106
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and transition programme component predictors of new graduate workplace integration

Abstract: Nurse managers are in key positions to advocate for new graduate nurse transition programmes with adequate resources to support a four week orientation phase and shift scheduling to ensure an adequate number of hours over two week periods to facilitate transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(127 citation statements)
references
References 34 publications
7
120
0
Order By: Relevance
“…This indicates that the students have perceived themselves to be more confident after the program. This outcome is concurrent with the study conducted by Rush, Adamack, Gordon, Janke, and Ghement [41] in that their finding indicated that a formal orientation-transition program had significantly higher total confidence scores than nurses that did not participate in the program.…”
Section: Discussionsupporting
confidence: 74%
“…This indicates that the students have perceived themselves to be more confident after the program. This outcome is concurrent with the study conducted by Rush, Adamack, Gordon, Janke, and Ghement [41] in that their finding indicated that a formal orientation-transition program had significantly higher total confidence scores than nurses that did not participate in the program.…”
Section: Discussionsupporting
confidence: 74%
“…Formal orientations assist in assimilating new employees into the organization by providing individuals with institutional information, such as policies and procedures manuals, introductions, and tours. 14,20 Orientation is one of the first steps of the onboarding process and therefore plays a very important role. Orientation programs facilitate the transition to practice by providing a comforting welcome, structured support, training through classroom learning and clinical experiences, preceptorship, measurement of progress, and evaluation of clinical competence.…”
Section: Suggestions For Orientationmentioning
confidence: 99%
“…Research 44 in nursing showed that longer orientations resulted in greater satisfaction and retention. Recently, new nursing graduates were examined 20 during the orientation and transition-to-practice process. A transition score was derived from the CaseyFink transition survey, which evaluated new nurses on 5 transition-to-practice constructs: organizing/prioritizing, communication/leadership, support, stress, and personal satisfaction.…”
Section: Length Of Orientationmentioning
confidence: 99%
See 2 more Smart Citations